Exploring the capital investment practice of mining corporations in Namibia - Iiyambo, Hilma Naleshemunyenga (Research of GSB, 2019)
Namibia is a country rich in minerals, and this has attracted both national and international investors to the mining industry in the country. The mining sector is a capital-intensive industry that calls for long-term investment. Capital investment is a long-term economic venture that requires and consumes a lot of resources, for example, the purchase of fixed assets, such as land, machinery, and buildings (Ward, 2013). Capital investment in the mining sector is risky because of various uncertainties that include among others, political risks, environmental risks (geological), fluctuations of mineral prices on the world market, changes in fiscal policies, and the depletion and exhaustion of mineral resources. Generally, risks associated with technical and commercial aspects have always been high in the mining sector (Bhapu, 2005). Because of the risky nature of the mining sector, companies venturing into a mining project need to adopt comprehensive capital investment practices that realise the return on capital, taking into cognisance all risks that could jeopardise and frustrate the ambitions of the promoters, shareholders and various stakeholders, which include the government, downstream industries and the local community. The aim of this study was to explore capital investment practices of mining corporations in Namibia focusing on the five large mining companies. The purpose was to identify gaps between investment practice and investment theory that might have a long-term impact on mineral dependent national economies, development finance for local community sustainable development and the return on capital to investors. Since large-scale mining demands large capital investment that requires proper long-term planning for the realisation of return on capital, it has been found necessary to purposively select five largest mining corporations for the study. The mining organisations involved were De Beers Marine, Rosh Pinah, Rössing, Tsumeb Corporation and Navachab. The study employed an exploratory qualitative research approach to explore the capital investment practices of five major mining operations in Namibia that generate more than 95% of the mining income. The study employed the qualitative research in order to obtain a deep understanding of capital appraisal methods used and get reasons why they are used. Purposive sampling was used to select five participants for the survey. The collected data was assessed and analysed using thematic analysis. The analysed data was converted into tables and bar charts. The tables and bar charts of analysed data are presented as findings in chapter four of this study. The results show that five of the mining organisations use Net Present Value to conduct capital investment appraisal and a similar number uses the Payback Back Period. Two of the mining organisations use IRR and one uses ARR for capital investment appraisal. It was further found that mining organisations surveyed factor in development finance in their capital budgeting process but experience unforeseen incidences when it came to implementation. Finally, it is recommended that the Government of Namibia together with various stakeholders consider and incorporate development finance in their capital investment appraisal and capital budgeting for sustainable development.